Land Disputes, Rights Assertion, and Social Unrest in China: A Case from Sichuan - Pils, Eva (Columbia Journal of Asian Law, 2005)
With social unrest intensifying in China, there is a growing sense that the legal reforms of the past two decades have failed to provide adequate channels for resolving conflicts of interest and viewpoint between government and citizens-especially those citizens who have been disadvantaged by economic development, and who believe that their legal rights have been violated in this process. As early as the autumn of 2003, Yu Meisun, a former official who had participated in the drafting of China’s 1989 Administrative Litigation Law, wrote: The Party and Government have been investing a great amount of human and material resources into the legal system since 1979, in order to protect the social order and resolve various conflicts in society. But this system has not only failed to serve the function it was supposed to serve, it has even been counterproductive, exacerbating conflicts. The assessment that legal reform has made things worse by “exacerbating conflicts” in China is understandable in its context. Yu’s writings about petitioning and administrative litigation cases convey a certain sense of hopelessness: people waste their lives seeking justice from state authorities, whose written or unwritten rules of operation sometimes seem designed to compound citizens’ grievances rather than to help redress them. Especially in cases of land requisitioning, the citizens’ own livelihoods as well as those of their children may be lost. Yet the case that led Yu to make this assessment is also indicative of a positive aspect of the legal reform process. The case cited by Yu can be seen as part of a broader trend of cases where the promise of a government limited by rights is being taken seriously, and rights are being asserted toward the government at different levels. Injustices are now met with resistance by people who invoke the law to challenge those claiming to act with legal authority.